2014
DOI: 10.1094/pdis-07-13-0753-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Fluopyram, Fluxapyroxad, and Penthiopyrad in Botrytis cinerea from Strawberry

Abstract: Succinate dehydrogenase inhibitors (SDHIs) constitute a mainstay in management of gray mold caused by Botrytis cinerea in strawberry and several other crops. In this study, we investigated the risks of resistance development to three newer SDHIs (i.e., fluopyram, fluxapyroxad, and penthiopyrad) and their cross-resistance with the previously registered boscalid. We investigated the mutations in the SdhB subunit and evaluated their impact on microbial fitness in field populations of B. cinerea. Amino acid substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 35 publications
2
79
1
Order By: Relevance
“…Different single-point mutations in sdh gene are involved in resistance mechanisms of B. cinerea for these compounds (Veloukas et al, 2011(Veloukas et al, , 2013Yin et al, 2011;Veloukas & Karaoglanidis, 2012;Amiri et al, 2014). Our data are in agreement with recent reports (Veloukas et al, 2013;Amiri et al, 2014) as boscalid-resistant isolates used in this study possessed H272R mutation in the SdhB subunit that display a differential sensitivity to the SDHIs (Lalève et al, 2013;De Miccolis Angelini et al, 2014a). Control efficacy of SDHI fungicides confirmed data obtained in vitro.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Different single-point mutations in sdh gene are involved in resistance mechanisms of B. cinerea for these compounds (Veloukas et al, 2011(Veloukas et al, , 2013Yin et al, 2011;Veloukas & Karaoglanidis, 2012;Amiri et al, 2014). Our data are in agreement with recent reports (Veloukas et al, 2013;Amiri et al, 2014) as boscalid-resistant isolates used in this study possessed H272R mutation in the SdhB subunit that display a differential sensitivity to the SDHIs (Lalève et al, 2013;De Miccolis Angelini et al, 2014a). Control efficacy of SDHI fungicides confirmed data obtained in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…The sensitivity to SDHIs was also tested in a conidial germination assay on WA, as previously described (Kim & Xiao, 2010;Amiri et al, 2014), for a subset of 14 B. cinerea isolates, selected according to different EC 50 values obtained from previous mycelial growth assays. The 5 μg mL −1 dose discriminated resistant from sensitive isolates.…”
Section: Determination Of Baseline Sensitivity To Fluopyram and Sensimentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the boscalid-resistant mutants had a base change (CCC ¡ CTC) which resulted in a P225L substitution in sdhB. This substitution has not been found in boscalid-resistant field strains of B. cinerea, which contained H272R, H272Y, H272L, N230I, and P225F substitutions instead (35,36; S. Rupp, unpublished data). Induced selection of carbendazim resistance in B. pseudocinerea resulted in the preferential occurrence of the F200Y mutation in ␤-tubulin, which is less common than the E198A mutation in field strains of B. cinerea (37).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to boscalid, the first SDHI molecule introduced as a botryticide, emerged soon after the onset of its use. Currently, resistance to SDHIs has been reported in B. cinerea populations originating from table grapes, strawberry, tomato, lettuce, kiwi fruit, and apple fruit in several European and North or South America countries (Bardas et al, 2010; Kim and Xiao, 2010; Leroux et al, 2010; Leroch et al, 2011; Veloukas et al, 2011; Fernandez-Ortuno et al, 2012; Chatzidimopoulos et al, 2013; Amiri et al, 2014; De Miccolis Angelini et al, 2014b; Hahn, 2014; Konstantinou et al, 2015). Sequence analysis of the four sdh subunits in SDHI-resistant strains revealed that resistance was associated with nine target site mutations located in the sdh B subunit and one mutation in the sdh D subunit.…”
Section: Introductionmentioning
confidence: 99%